How Nanofibers Carry the Load: Toward a Universal and Reliable Approach for Tensile Testing of Polymeric Nanofibrous Membranes. Issue 7 (16th July 2021) - Maccaferri, Emanuele; Cocchi, Davide; Mazzocchetti, Laura; Benelli, Tiziana; Brugo, Tommaso Maria; Giorgini, Loris; Zucchelli, Andrea
Abstract : Back Cover : Mechanical properties assessment of nanofibrous nonwovens is complex due to their porous morphology and soft nature, possibly leading to inaccurate results. In article number 2100183 by Laura Mazzocchetti, Andrea Zucchelli, and co‐workers, the high reliability of mass‐based normalization of load with respect to the cross‐section is proposed and demonstrated using Nylon 66 nanofibers, providing a simple, effective, and universally suitable method for obtaining highly reproducible tensile stress–strain curves.